The Hybrid Genome of a New Goldfish-Like Fish Lineage Provides Insights Into the Origin of the Goldfish - Wang, Yude; Tan, Huifang; Zhang, Minghe; Zhao, Rurong; Wang, Shi; Qin, Qinbo; Wang, Jing; Zhang, Chun; Tao, Min; Ma, Ming; Chen, Bo; Liu, Shaojun (Frontiers in Genetics, 2020)
Distant hybridization leads to obvious changes in genotypes and phenotypes, giving rise to species with novel capabilities. However, the fusion of distinct genomes also converges the DNA or gene variations that occur during the course of evolution. Knowledge of the early stages of post-hybridization evolution is particularly important, because changes during these stages have long-term evolutionary consequences. Here, we investigated the full-length (FL) tr anscriptomes and the sequences resulting from the genome resequencing of the red crucian carp-like fish (RCC-L) and goldfish-like fish (GF-L) derived from the interspecific hybridization of koi carp (KOC) and blunt snout bream (BSB) to provide molecular evidence for the hybrid origin of the goldfish (GF). We compared the orthologous genes in the transcriptomes of RCC-L and GF-L with those of KOC and BSB. We also mapped the orthologous genes to the common carp (CC) and BSB genomes and classified them into eight gene patterns in three categories (chimaera, mutant, and biparental origin genes). The results showed that 48.20% and 46.50% of the genes were chimaera and that 3.70% and 8.30% of the genes were mutations of orthologous genes in RCC-L and GF-L, respectively. In RCC-L and GF-L, 63.70% and 68.20% of the genetic materials were from KOC, and 12.30% and 11.90% of the genetic materials were from BSB. The sequences from the genome resequencing of RCC-L and GF-L were mapped to the genome sequences of CC and BSB, revealing that the similarities of both RCC-L and GF-L to the CC genome (92.52%, 90.18%) were obviously higher than to the BSB genome (50.33%, 49.18%), supporting the suggestion that the genomes of both RCC-L and GF-L were mainly inherited from KOC but had some DNA fragments from BSB. Overall, our results provide molecular biological evidence for the hybrid origin of red crucian carp (RCC) and GF.